2014
DOI: 10.1111/vru.12180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ear Disease in Dogs Undergoing Multidetector Thin‐slice Computed Tomography of the Head

Abstract: Previous reports describing the prevalence of ear diseases in dogs have primarily been based on dogs presenting with clinical signs of disease. The prevalence of subclinical ear disease remains unknown. The purpose of this cross-sectional retrospective study was to describe the prevalence of lesions consistent with middle and external ear disease in dogs presented for multidetector computed tomography (CT) of the head and/or cranial cervical spine at our hospital during the period of July 2011 and August 2013.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 18 publications
6
28
3
Order By: Relevance
“…Although it is impossible to be sure of the constitution of the bulla contents without myringotomy, examination and analysis of the fluid/tissue, it seems likely that the material observed in the middle ear of brachycephalic dogs represents noninflammatory fluid as none of the dogs had clinical signs of otitis media or other imaging findings suggesting inflammation. In other publications, the incidence of dogs with subclinical otitis media varied from 12.5% to 41%, with a higher prevalence in brachycephalic dogs (Cavalier King Charles spaniels, Bulldogs, and Boxers), mainly reported with MRI . Our results support the predisposition of brachycephalic dogs to having subclinical middle ear disease.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although it is impossible to be sure of the constitution of the bulla contents without myringotomy, examination and analysis of the fluid/tissue, it seems likely that the material observed in the middle ear of brachycephalic dogs represents noninflammatory fluid as none of the dogs had clinical signs of otitis media or other imaging findings suggesting inflammation. In other publications, the incidence of dogs with subclinical otitis media varied from 12.5% to 41%, with a higher prevalence in brachycephalic dogs (Cavalier King Charles spaniels, Bulldogs, and Boxers), mainly reported with MRI . Our results support the predisposition of brachycephalic dogs to having subclinical middle ear disease.…”
Section: Discussionsupporting
confidence: 84%
“…C omputed tomography (CT) and magnetic resonance imaging (MRI) examinations of the head in dogs and cats frequently detect subclinical tympanic bulla lesions, with a reported prevalence up to 41% in dogs . Computed tomography and MRI have been previously established as accurate methods for identification of fluid within the canine tympanic bulla .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of middle ear CT lesions in the current study was 32.9%. This is higher than a previous study where the prevalence of otitis media was reported as 19.5% in dogs presented for CT scan of the head or cervical spine . However, comparison should be considered cautiously because the reasons for referring cases for CT can vary amongst referring veterinarians.…”
Section: Discussioncontrasting
confidence: 58%
“…The availability, cost, shorter scanning time and the maximized visualization of bony structures make high‐resolution CT the method of choice in the imaging of the middle ear in humans . Computed tomography has been proposed as an alternative to evaluate middle ear structures in animals . This noninvasive diagnostic technique allows visualization of anatomic structures in cross‐section, while avoiding the superimposition of ear structures, which occurs on radiographs.…”
Section: Introductionmentioning
confidence: 99%